Moral deliberation of nurses regarding hospitalization by court order - Kely Regina da Luz; Mara Ambrosina de Oliveira Vargas; Edison Luiz Devos Barlem; Dulcinéia Ghizoni Schneider; Franciele Budziareck das Neves (Universidade Federal de Santa Maria, 2019)
Aim: to analyze the ethical problems experienced by intensive care nurses in situations of hospitalization by judicial order in the perspective of moral deliberation. Method: qualitative research carried out between January and December 2016, through semi-structured interviews with 42 intensive care nurses from South and Southeast regions of Brazil. Interpreted through Discursive Textual Analysis. Results: the analysis resulted in three categories that present in their content the priority of deliberation, the moral suffering of nurses and the nurse's advocacy. Final considerations: health judicialization brings significant changes in social and institutional relations. Nurses must realize that, facing the different possibilities of decision-making in the face of ethical problems, important moral values are in conflict.